Constructing Psychological Exhaustion Scale for the Athletic-Activity Practitioners from the Students of Mosul University - Ahmed Hazim Al-Ta (مجلة الرافدين للعلوم الرياضية, 2014)
The research aims at : - Constructing psychological exhaustion scale for the athletic-activity practitioners from the students of Mosul university - Recognizing the level of psychological exhaustion level for the athletic-activity practitioners from the students of Mosul university - Establishing standard levels for the athletic-activity practitioners from the students of Mosul university in the psychological exhaustion scale. The researchers have adopted the descriptive methodology with a survey style . The research community includes the students practicing athletic activities in Mosul university as (1686) students distributor into all colleges of Mosul university except college of education for girls because were no male students . The research sample has been divided into two samples : the construction sample represented by (1096) students at an average (65%) , and the application sample represented by (590) students at an average (35%). The psychological exhaustion scale that which was prepared by the researchers will be used as a tool of collecting data . On the other hand , the construction procedures were : ( determining the scale dimensions , determining the style of scale items , formulating the items of each dimension in its initial form , in addition to adopt the scientific steps and procedures in constructing the scale including the content validity , Face validity of the scale , the construction validity represented by ( the statistical analysis of the items ) with both styles of the contradictory groups , and the internal consistency ). Also, the re-test for reliability was used . The statistical tools were ( the arithmetic mean , mode , standard deviation , coefficient of skewenss equation of ( Karl Pearson ) , simple correlation coefficient , t-Test, the assumptive mean of the scale and the percentage ). The following is an explanation of the concept of psychological exhaustion: • Exhaustion linguistically means exaggeration in act and it associates with fatigue and dedication to work . • It means no adoption to work and Indicates that the individual fancies that his work something mischievous threatening and unsaturated him . So, the individual often becomes tired and bored of that work . Mostly , his subconscious destination is to change the quality of the work . • The psychological exhaustion of the individual is resulted from the exposure to the constant pressures that excess his ability . • It represents a negative case and response to the others. • It leads to physical exhaustion , emotional exhaustion , lack of a sense of personal achievement , and the negative self-evaluation . • It differs from person to another because of the individual differences and the difference of the psychological energy from one to another . • It occurs to those who work and connect to people ,i.e. working in the field of human and social services . There were three dimensions of the psychological exhaustion : the emotional exhaustion , emotional change , and lack of a sense of personal achievement . According to that , the psychological exhaustion can be theoretically defined “ it is a case that occurs to the individual because of the pressures ,excessive load and the inability to be in compatible with it , which leads to the emergence of a group of multiple manifestations that include most aspects of life .This influences on the individual view to himself and the others .